TEACHING REPORT PARAGRAPH WRITING BY USING PIE (POINT, ILLUSTRATION, EXPLANATION) STRATEGY TO THE ELEVENTH GRADE STUDENTS OF MAN 1 PALEMBANG - Muhammad Yusuf (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2015)
The aim of this study was to find out whether or not there is any means significant difference on students writing achievement of PIE (Point, Illustration, Explanation) and those who are not to eleventh grade students in MAN 1 Palembang. The population of this study consisted of 209 eleventh grade students of MAN 1 Palembang in academic year 2014/2015. The sample was selected by using purposive sampling. There were 76 students selected. Before being taught writing by using Pie Strategy or given treatment, the students were given pretest. From the students’ score pretest, the writer got XI science 3 lower than XI science 2, it means that XI science 3 become as a experimental group and XI science 2 become as a control group. This study was conducted for about one month. During the treatment, the experimental group taught by using Pie strategy. There were twelve meetings which spent 70 minutes (2x35 minutes) in each meetings. Every meetings they got writing materials that were taken from Senior High School English books, cyberspace, and students’ environment for the eleventh grade students. The data were in form of posttest experimental and control group of students writing achievement scores. Then, they were analyzed by using independent sample t-test to meet the objective of the study. From the result of independent sample t-test, it was found that there was a significant difference from students posttest experimental and control group, since the p-output was lower than 0.05 and t-value was higher than t-table (1.66).